Setup Time Reduction for Hot Pressing Mold Changeover - Lerdsakwanich, Ponlapas; Klomjit, Prachuab (Frontiers in Engineering Innovation Research, 2020)
This research aims to reduce setup time and to improve the mold changeover process in disc brake manufacturer. Certainly, the shape of the disc brakes varies according to the car model. That is why the production is required to include mold changeover process. The research findings indicate that mold changeover has an average of 15 times a day in the hot-pressing process which takes the longest time to set up the machine. As the researchers, we performed examination on the procedures and time spent on mold changeover by work and direct time study principles and analyzed the ways to improve the processes by applying the SMED concept with 5W1H questions. The study found that there are 6 activities that can be taken while the machine is operating that including 1 non-value added (NVA) activity and 5 necessaries but non-value added (NNVA) activities. In addition, approximately 70 percent of overall setup time was spent on uninstallation of the old mold and reinstallation of the new one. Therefore, this study applied the ECRS principles to improve activity for mold changeover. As a result, the activities have been reduced from 10 activities to 6 activities while the setup time has plummeted from 946.2 seconds to 492.8 seconds, which resulted in 52 percent decrease in setup time. After performing calculations on the optimal number of times and assessment of the normality of data by Minitab at the confidence level of 95% and the tolerance of ±5%, the results show that the number of basic laps in the 30 timings is appropriate and the data has a normal distribution. The average time of data can be representative of the group. Therefore, after the process improvement, the total average time is considerably decreased and is compliant with the standard of company.